Legal Protection for Indonesian Migrant Workers in the Domestic Sector in Brunei Darussalam - Purnamasari, Wita; Sulaiman, Abdullah; Redi, Ahmad (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The protection of Indonesian Migrant Workers (PMI) abroad, particularly in Brunei Darussalam, is crucial to ensure their rights and welfare. Despite existing regulations such as Law Number 18 of 2017, PMIs continue to face various challenges including exploitation, unpaid wages, and violence. Addressing these issues requires a comprehensive approach involving legal, social, and diplomatic efforts. Purpose. This study aims to analyze the legal protections available to Indonesian Migrant Workers in Brunei Darussalam. It seeks to identify the effectiveness of current legal frameworks, the roles of Indonesian governmental institutions, and the impact of bilateral agreements between Indonesia and Brunei in safeguarding the rights of PMIs. Method. Utilizing a juridical-normative methodology, this research examines the legal documents, regulations, and policies related to PMI protection. It also analyzes case studies and statistical data on PMI cases in Brunei, focusing on the roles of BP2MI, the Ministry of Manpower, and the Ministry of Foreign Affairs. Results. The findings reveal that while legal frameworks exist to protect PMIs, there are significant gaps in implementation and enforcement. Bilateral agreements between Indonesia and Brunei need to be strengthened, and there is a need for more effective legal assistance and support systems for PMIs. The study also highlights the critical role of the Indonesian Embassy in providing on-ground support to PMIs. Conclusion. Comprehensive protection of Indonesian Migrant Workers in Brunei requires a multi-faceted approach. This includes stronger bilateral relations, improved regulatory frameworks, and active support from Indonesian government institutions. Ensuring the rights and welfare of PMIs will require ongoing collaboration between Indonesia and Brunei, as well as continuous monitoring and evaluation of the effectiveness of legal protections.